Cloning of DNA: A Review - Hammadi, Amer A.; Al-Mousawi, Masar R. R. (Scientific Journal of Medical Research, 2021)
Objective: The advantage of molecular cloning show similarity of the chemical structure of DNA in all living creatures is fundamental as the main fact. As a result, in case any DNA fragment from any creatures is introduced into a DNA sequence essential for DNA replication, it will cause DNA replication, the foreign DNA will be reproduced alongside the host cell’s DNA in the transgenic organism when the recombinant DNA is injected to the creatures to derive the replication sequences. In that, it allows the replication of DNA sequences to be comparable to a polymerase chain reaction (PCR) with molecular cloning. The primary distinction amidst two approximations is that DNA replication is one step of molecular cloning in a living microorganism, whereas in vitro DNA replicates in living cells PCR by PCR. Conclusion: Individual DNA fragments extracted by scientists through molecular cloning infinite number of from any genome. This substance can exist utilized in applied and basic applications in biological science.